A universal approach for integrating super large-scale single-cell transcriptomes by exploring gene rankings. Issue 2 (20th January 2022) - Shen, Hongru; Shen, Xilin; Feng, Mengyao; Wu, Dan; Zhang, Chao; Yang, Yichen; Yang, Meng; Hu, Jiani; Liu, Jilei; Wang, Wei; Li, Yang; Zhang, Qiang; et al.
Abstract: Advancement in single-cell RNA sequencing leads to exponential accumulation of single-cell expression data. However, there is still lack of tools that could integrate these unlimited accumulations of single-cell expression data. Here, we presented a universal approach iSEEEK for integrating super large-scale single-cell expression via exploring expression rankings of top-expressing genes. We developed iSEEEK with 11.9 million single cells. We demonstrated the efficiency of iSEEEK with canonical single-cell downstream tasks on five heterogenous datasets encompassing human and mouse samples. iSEEEK achieved good clustering performance benchmarked against well-annotated cell labels. In addition, iSEEEK could transfer its knowledge learned from large-scale expression data on new dataset that was not involved in its development. iSEEEK enables identification of gene–gene interaction networks that are characteristic of specific cell types. Our study presents a simple and yet effective method to integrate super large-scale single-cell transcriptomes and would facilitate translational single-cell research from bench to bedside.